Effect of basic life support training programme on knowledge and practice among administrative employees of health institutes, Navi Mumbai - Ravindra Sansare, Kshama; Jacob , Susan (Innovational: Journal of Nursing and Healthcare, 2024)
Background: Basic Life Support (BLS) competency is considered a fundamental skill not only for health care workers but also for other non-medical personnel such as administrative employees. Administrative employees are the people who are working for 24 hours in the hospital along with healthcare professionals. Patients who are visiting hospitals first come to the inquiry desk for inquiry and meet the non-medical personnel, such as administrative staffs; In case any person falls there with cardiac arrest the administrative staff should have some knowledge and practice regarding BLS to save the life of that person before the medical team arrives. Aim: The objectives of the study are to assess the knowledge regarding Basic Life Support among administrative employees before and after the training programme and to assess the practice regarding Basic Life Support among administrative employees before and after the training programme. Materials and methods: Quantitative research approach and quasi-experimental one group pre-test post design was used. The non probability convenient sampling method was used to select 60 administrative employees as a study subject. Results and conclusion: The mean knowledge score of subjects in pre-test was 4.90 and in post-test was 9.78 and overall mean practice score of subjects in pre-test was 3 and in post-test 16.15. There is no significant association between pre-test knowledge and practice score in relation to BLS and selected aspects of socio-demographic variables. Equal positive response to the demonstration and teaching was found really useful to administrative employees who will help them to take prompt decisions, perform cardiopulmonary resuscitation and save many lives of cardiac arrest victims.